Clinical Patterns of Pharmacotherapy Administration in Acute Heart Failure at a Tertiary Hospital in Indonesia - Nadhifa Ainur Rohmah; Andrianto Andrianto; Sundari Indah Wiyasihati; Anudya Kartika Ratri (Universitas Airlangga, 2026)
Highlights: Diuretics were the most commonly administered therapy for AHF patients. Pharmacotherapy administration adhered to the existing European Society of Cardiology (ESC) and the Indonesian Heart Association (PERKI) guidelines. Abstract Introduction: Acute heart failure (AHF) has long been the leading cause of hospitalizations among the elderly. In Indonesia, AHF poses a significant challenge due to its high rates of hospitalization and mortality, with the number of cases continuing to rise annually. This study aimed to characterize the clinical pharmacotherapy patterns of AHF patients during hospitalization at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, providing valuable insights into therapeutic approaches in this tertiary care setting. Methods: This retrospective descriptive study utilized secondary data from medical records of AHF patients admitted to Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, between January and December 2023. This study included 52 patients aged 18 years and older with complete medical records. All statistical procedures were performed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 25.0 to support systematic and reproducible evaluation of the dataset. Results: This study categorized AHF treatment based on clinical manifestations, etiology, and ejection fraction. Diuretics were the most commonly used medication across all categories. Patients with acute decompensated heart failure (ADHF) and acute pulmonary edema primarily received diuretics and vasodilators, while inotropes were administered for isolated left ventricular failure. Patients with cardiogenic shock were treated with vasopressors and inotropes. Treatment patterns highlighted the tailored use of additional therapies, including vasodilators and vasopressors, according to specific clinical presentations and ejection fraction profiles. Conclusion: All medications administered to AHF patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January to December 2023 adhered to existing guidelines.